1981
DOI: 10.1159/000166485
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular IgE Deposits in Patients with Lupus Nephritis

Abstract: The presence of glomerular IgE deposits (IgE+) and its prognostic significance were examined in 241 patients with various renal diseases. 24 patients (10%) had IgE+, and nephrotic syndrome was present in 22 (92%). 17 of the 24 patients with IgE+ had lupus nephritis. These patients were compared with another group of 32 patients with lupus nephritis, but without IgE deposits (IgE-). Light and electron microscopy showed more severe pathological changes in those with IgE+ than in patients who were IgE-. The numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 6 publications
1
16
1
Order By: Relevance
“…A possible pathogenic role of IgE antibodies in lupus nephritis has been claimed by some research groups that observed an increased serum concentration of this immunoglobulin in renal SLE patients (4,10). Additionally, IgE was detected in glomerular deposits of immune complexes by immunofluorescence assays of kidney biopsies from renal SLE subjects (18,19). In the present study, 5 of 8 SLE patients with laboratory findings of renal disorders such as proteinuria, hematuria and urinary cellular casts had high serum IgE concentrations and 6 of them had antinuclear IgE autoantibodies.…”
supporting
confidence: 51%
“…A possible pathogenic role of IgE antibodies in lupus nephritis has been claimed by some research groups that observed an increased serum concentration of this immunoglobulin in renal SLE patients (4,10). Additionally, IgE was detected in glomerular deposits of immune complexes by immunofluorescence assays of kidney biopsies from renal SLE subjects (18,19). In the present study, 5 of 8 SLE patients with laboratory findings of renal disorders such as proteinuria, hematuria and urinary cellular casts had high serum IgE concentrations and 6 of them had antinuclear IgE autoantibodies.…”
supporting
confidence: 51%
“…The latter authors state that, through the release of vasoactive mediators from basophils and mast cells, IgE can cause increased vasopermeability, which may be important in causing the deposition of circulating immune complexes in glomerulonephritis pathogenesis (28),(29). The demonstration of increased IgE serum levels in SLE patients with renal involvement and the detection of IgE immune complex deposition in renal biopsies further implicate IgE in the pathogenesis of lupus nephritis (13),(29),(30). High IgE levels have also been reported in adult SLE patients without nephritis, suggesting that IgE may have a role in SLE disease and not only in nephritis (4),(12),(14),(15),(31),(32).…”
Section: Discussionmentioning
confidence: 91%
“…Other antisera which have been used include those to IgE [247], kappa and lambda lights chains, renal tubular components, hepatitis B antigen, DNA, properdin, carcinoembryonic antigen, various bacterial and parasitic antigens and several components of the complement system, particularly Clq [137,248]. A control specimen of renal tissue with known staining characteristics should be included with each procedure.…”
Section: Methodsmentioning
confidence: 99%